A strategic framework for countering terrorism and insurgency - Hoffman, Bruce, 1954-; Taw, Jennifer M., 1964-; National Defense Research Institute (U.S.). International Security and Defense Strategy Program; Rand Corporation; United States. Department of State (Santa Monica, CA : RAND, 1992)
The strategies and tactics used by governments to counter terrorism and insurgency vary widely, from highly visible declarations of states of siege, for example, to less visible measures such as covert operations. In the absence of a national plan, the individual application of selected tactics and policies can do more harm than good. Governments must develop a plan that acknowledges all the elements of a counterterrorism or counterinsurgency campaign. There are four elements, used singly or in combination, that successful campaigns contain regardless of geographic regions, time periods, and political systems: (1) command and coordination; (2) effective antiterrorist legislation combined with measures to build public trust and support; (3) coordination within and between intelligence services; and (4) foreign collaboration amongst governments and security forces. This study examines the way these elements were applied across seven case studies, draws conclusions about the relative utility of different elements under various circumstances, and makes suggestions for future counterinsurgency and counterterrorism campaigns. The case studies include the three key British counterterrorist/counterinsurgency campaigns of the 1940s and 1950s involving Malaya, Kenya, and Cyprus; the more recent struggle in Northern Ireland; the 1965-1980 Rhodesian conflict; and the counterterrorist experiences of Germany and Italy during the 1970s and 1980s.
Research conducted "within the International Security and Defense Strategy Program of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references (p. 141-146).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Counterinsurgency -- Case studies; Insurgency -- Case studies; Reprisals; Terrorism -- Prevention -- Case studies